Helping children and young people who self harm : an introduction to self-harming and suicidal behaviours for health professionals - McDougall, Tim (Routledge, 2010)
Every year thousands of children and young people attend emergency departments with problems resulting from self-harm. This title provides practical guidance for health professionals and other members of the children's workforce who are confronted by this complex and difficult area. It looks at what we mean by self-harm and its prevalence.